BaliMall.id Integrated Marketing Communication Strategy in Building a Brand Image as an E-Marketplace by Balinese People - Wiweka, Ida Bagus Satia; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 3 No 1 (2022): Jurnal Ilmu Komunikasi Vol 3 No 1 Tahun 2022, 2022)
Brand image is a very important factor for new businesses to attract customer or users, one of which is BaliMall.id. The purpose of this research is to see BaliMall.id's integrated marketing communication strategy in building a brand image as an E-Marketplace created by Balinese people. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. In this study, the key informants were the CEO, the Public Relations staff, and the user. The data analysis used in this research is qualitative. BaliMall.id uses integrated marketing communications to support success in building a brand image which are advertising, sales promotion, direct marketing and internet marketing, public relations, personal selling, Event and Experience, and Word of Mouth. Keywords:, E-Marketplace, brand image, integrated marketing communication